The Gradual Dependence on Starlink and Its Impact on the Digital Organization of Arctic Territories in Canada - Rabouam, Célestine R. (Global Governance of Low Earth Orbit Satellites, 2025)
This chapter analyzes the implications of increased reliance on Starlink satellite broadband in remote Arctic regions of Canada. It explores how LEO connectivity shapes digital sovereignty, community autonomy, and service provision among Indigenous populations. Drawing from field data and policy analysis, it critically reflects on the long-term governance and equity issues in northern digital infrastructure planning.